2015
DOI: 10.1111/andr.310
|View full text |Cite
|
Sign up to set email alerts
|

Low testosterone is associated with poor health status in men with human immunodeficiency virus infection: a retrospective study

Abstract: SUMMARYMen with human immunodeficiency virus (HIV) infection are often hypogonadal and develop several HIV-associated nonacquired immunodeficiency syndrome (AIDS) (HANA) conditions that impair overall health status. No studies explored the relationship between health status and serum testosterone (T) in HIV-infected men. This study aims to investigate the association between total serum T and HANA, multimorbidity, and frailty in a large cohort of 1359 HIV-infected men and to explore the relationship between pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 53 publications
9
42
0
Order By: Relevance
“…The pathogenesis of hypogonadotropic hypogonadism in HIV-infected men is multifactorial and androgen deficiency is more often a consequence of secondary hypogonadism than primary hypogonadism (2,3,4,5,7,8); causes of hypogonadotropic hypogonadism in HIVinfected men include undernutrition, severe illness, drugs (psychotropics, opiates, megestrol acetate or steroids), pituitary dysfunction (tumor, hyperprolactinemia), an AIDS-related lesion (very rarely), the HIV virus replication and co-morbid conditions, such as antibody to hepatitis C virus seropositivity and injection drug use (2,3,4,5). Also, HAART, particularly protease inhibitor therapy has been associated with sexual dysfunction in men, but the causal nature of this relation has not been clearly established as many of these patients have normal testosterone levels and some studies have demonstrated that initiation of HAART, including protease inhibitor, can restore testosterone levels to normal (2,3,6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pathogenesis of hypogonadotropic hypogonadism in HIV-infected men is multifactorial and androgen deficiency is more often a consequence of secondary hypogonadism than primary hypogonadism (2,3,4,5,7,8); causes of hypogonadotropic hypogonadism in HIVinfected men include undernutrition, severe illness, drugs (psychotropics, opiates, megestrol acetate or steroids), pituitary dysfunction (tumor, hyperprolactinemia), an AIDS-related lesion (very rarely), the HIV virus replication and co-morbid conditions, such as antibody to hepatitis C virus seropositivity and injection drug use (2,3,4,5). Also, HAART, particularly protease inhibitor therapy has been associated with sexual dysfunction in men, but the causal nature of this relation has not been clearly established as many of these patients have normal testosterone levels and some studies have demonstrated that initiation of HAART, including protease inhibitor, can restore testosterone levels to normal (2,3,6).…”
Section: Discussionmentioning
confidence: 99%
“…Since HIV therapy is now initiated at earlier stages of HIV infection than in the past, the prevalence of hypogonadism is lower, being present in about 20% of men who receive HAART (4,5). Hypogonadism in HIV-infected men presents similarly to androgen deficiency in the general population and is characterized by loss of facial and body hair, decreased muscle mass and strength, high percentage of body fat, low libido, erectile dysfunction, testicular atrophy, infertility and sometimes gynecomastia (2,3,6,7,8,9,10). Depression, fatigue, low energy, poor concentration, mild anemia and low bone mineral density with osteoporotic fractures may also occur (2,3,6,7,8,9,10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 With this in view, a considerable quote of LOH are not consistent with a clinical condition of hypogonadism, but represents an epiphenomenon of a poor health status, which is a common condition in the elderly. 38,40 With this in view, hypogonadism could be considered as a functional, adaptive mechanism enrolled in presence of a condition of poor health status, 40,50,165,166 as it happens in case of acute, severe illness.…”
Section: Hypogonadism and Non-infectious Comorbiditiesmentioning
confidence: 99%